Speak to Sell: Pelatihan Singkat Presentasi Produk dalam Bahasa Inggris Untuk Siswa SMK - Fatima Kamila; Dian Nur Endah; Junita Dwi Purwandari; Ery Mulfias Yuli (Civiliza Publishing, 2025)
Public speaking skills using English are still a major challenge for Vocational High School students in Indonesia, even though these skills are needed in the competitive world of work. Therefore, this Community Service Program is carried out to design and implement training programs that focus on strengthening students' professional communication. The purpose of this activity is to improve the English language skills of Vocational High School students, especially in the aspects of public speaking and presentation skills. The program is implemented at SMK Media Informatika using a project-based learning approach combined with group discussions, where students design imaginary products and present them in English. Scientifically, this activity contributed to the development of a project-based product presentation training model for vocational education contexts that integrates language reinforcement, professional communication, and job readiness in a single applied training design. This model has the potential to be replicated as an evidence-based service approach to improving the communication competence of vocational school students.